Topical tocopherol for treatment of reticular oral lichen planus: a randomized, double‐blind, crossover study. (15th September 2016) - Bacci, C; Vanzo, V; Frigo, AC; Stellini, E; Sbricoli, L; Valente, M
Abstract : Objective: This randomized, double‐blind, placebo‐controlled crossover study assessed the efficacy of topical tocopherol acetate compared with placebo in easing oral discomfort in patients with reticular oral lichen planus (ROLP). Materials and Methods: Thirty‐four patients with clinically diagnosed and histologically confirmed ROLP were randomly assigned to two groups, which received first one of two treatments (treatment 1 or 2) for a month, then the other (treatment 2 or 1) for another month, with a two‐week washout between them. One treatment contained tocopherol acetate and the other only liquid paraffin. The primary outcome was less discomfort, measured on a visual analog scale (VAS). Secondary outcomes were as follows: length of striae measured and photographed at each follow‐up; surface area of lesions; and a modified Thongprasom score. Results: No statistically significant differences emerged between the two treatments (1 vs 2) in terms of VAS scores ( P > 0.05; 0.8624) or length of striae ( P = 0.0883). Significant differences were seen for surface area of lesions ( P < 0.05, P = 0.0045) and modified Thongprasom scores ( P = 0.0052). Conclusion: The two treatments differed only in terms of the surface area of the lesions and Thongprasom scores, not in VAS scores for discomfort or the length of patients' striae. Topical tocopherol proved effective in the treatment of ROLP.